Mapping the sensory values in the core zone area of Melaka world heritage site - Abd Rahman, Nur Hidayah; Ismail, Hairul Nizam; Khalifah, Zainab (IGU Tourism Commission, 2019)
The influence of sensory experience in generating positive tourist experience has emerged to be a cutting- edge trend in studies pertaining to geography and marketing in tourism, particularly in terms of tourism sense-making. The literature has projected absence of the fundamental comprehension related to the formation of ‘tourist space’ via tourist consumption and valuation towards available cultural heritage attractions based on their sensory experience. Critical shift in the objectivism approach from the light of valuing sensory experience has motivated the exploration of survey mapping method in this study. Hence, this study employed the survey mapping method derived from the landscape planning approach, in which a guide map was designed for international tourists to value each attraction during their visit at the Core Zone Area of Melaka World Heritage Site. The data gathered from 268 respondents were classified into five sensory mappings that reflected the concentration of sensory values of visual, gustatory, auditory, olfactory, and tactile perceptions. Visualisation of sensory mapping had been based on the classification of positive, moderate, and negative sensory values. The outcomes from these sensory mappings signify the notion of ‘tourist space’ or ‘honey pot’ among tourists based on their sensory experiences in the Core Zone area of Melaka World Heritage Site. This exploration of the survey mapping method has contributed to a critical discussion on the methodological approach, whereby most studies concerning sensory experience are dominated by the qualitative approach. Therefore, the study results could strengthen the management and planning by highlighting the significance of sensory quality in conserving and preserving momentous cultural heritage attractions.